Isolation and characterization of Klebsiella pneumoniae from medical waste and adjoining community water - Selim, Sadia Binte; Tabassum, Nuzhat; Ananna, Jannatul Nayeem (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.